Message from the Executive Director - Downey, Chris (Operating Room Nurses Association of Canada Journal, 2024)
The resumption of our webinar presentations in September reminded me of how quickly this year has passed. The Perioperative Nurses Week Contests for video and written submissions have been declared and a new cycle has begun. Congratulations to our winners for 2022!